Spatial distribution of N-cycling microbial communities showed complex patterns in constructed wetland sediments - Correa Galeote, David (2012)
Constructed wetlands are used for biological treatment of wastewater from agricultural lands carrying pollutants such as nitrates. Nitrogen removal in wetlands occurs from direct assimilation by plants and through microbial nitrification and denitrification. We investigated the spatial distribution of N-cycling microbial communities and genes involved in nitrification and denitrification in constructed wetland sediments receiving irrigation water. We used quantitative real-time PCR (qPCR) to characterize microbial communities. Geostatistical variance analysis was used to relate them with vegetation cover and biogeochemical sediment properties. The spatial distribution of the N-cycling microbial communities of sediments was heterogeneous and complex. Total communities of bacteria and crenarchaea showed different spatial distributions. Analysis of autocorrelation patterns through semivariance indicated a tendency towards a patchy distribution over scales around 10 m for genes involved in the nitrification and denitrification processes. In contrast, biogeochemical sediment properties showed diverse spatial distributions. While almost no patchiness was found for pH and moisture, patchiness at scales between 8 and 10 m was detected for carbon, nitrate and ammonia. Denitrification variables showed spatial autocorrelation at scales comparable to genes. However, denitrifying enzyme activity and potential N2O production showed a common spatial pattern, different from that of the N2O/(N2O + N2).